ANALISIS PERBEDAAN HARGA SAHAM, VOLUME PERDAGANGAN SAHAM, RETURN SAHAM SEBELUM DAN SESUDAH INFORMASI RENCANA AKUISISI PT. BANK TABUNGAN NEGARA (PERSERO) Tbk. OLEH PT. BANK MANDIRI (PERSERO) Tbk. - Andika Putra Pratama; Saryadi Saryadi; Sendhang Nurseto (Universitas Diponegoro, 2015)
Merger business in the form of acquisition becomes one of the strategies which strengthen capitalization of the bank in order to survive and compete. This thing becomes the basic consideration of Indonesia government to carry out an acquisition of PT. Bank Tabungan Negara (Persero) Tbk. by PT. Bank Mandiri (Persero) Tbk. The purpose of this research is to find out if there is any differentiation among stock price, stock trading volume and stock return before and after acquisition planning information PT. Bank Tabungan Negara (Persero) Tbk. by PT. bank Mandiri (Persero) Tbk. The result of the research reveals that there is no significant differentiation between stock price average of PT. Bank Tabungan Negara (Persero) Tbk. and PT. Bank Mandiri (Persero) Tbk. before and after acquisition planning information, there is no significant differentiation in stock trading volume average of PT. Bank Tabungan Negara (Persero) Tbk. before and after acquisition planning information, there is significant differentiation in stock trading volume of PT. Bank Mandiri (Persero) Tbk. before and after acquisition planning information, then, there is no significant differentiation between abnormal return average of PT. Bank Tabungan Negara (Persero) Tbk. and PT. Bank Mandri (Persero) Tbk. before and after acquisition planning information.